Idolatry and the colonial idea of India :visions of horror, allegories of enlightenment - Swagato Ganguly (South Asian history & culture, 2018)
This book explores literary and scholarly representations of India from the 18th to the early 20th centuries in South Asia and the West with idolatry as a point of entry. It charts the intellectual horizon within which the colonial idea of India was framed, tracing sources and genealogies which inform even contemporary descriptions of the subcontinent.